Effect of different anaesthetic techniques on the prognosis of patients with colorectal cancer after resection: a systematic review and meta-analysis - Xia, Shijun; Zhu, Yuwen; Wu, Wenjiang; Li, Yue; Yu, Linchong (Frontiers in Oncology, 2024)
Background: The effect of total intravenous anaesthesia (TIVA) and inhalation anaesthesia (IA) on the prognosis of patients with colorectal cancer after resection is controversial. This study aimed to explore the effects of different anaesthesia methods on the postoperative prognosis of colorectal cancer. Methods: PubMed, Embase and Cochrane Library databases were searched for relevant literature from each database's inception until 18 November 2023. The literature topic was to compare the effects of TIVA and IA on the prognosis of patients undergoing colorectal cancer resection. Results: Six studies were selected for meta-analysis. The studies involved 111043 patients, with a trial size of 1001-88184 people. A statistically significant difference was observed in the overall survival (OS) between colorectal cancer patients administered TIVA and IA (hazard ratio [HR], 0.83; 95% confidence interval [CI], 0.70-0.99), but none in recurrence-free survival (RFS) (HR, 0.99; 95% CI, 0.90-1.08). In the subgroup analysis of OS, no statistically significant difference was observed between colorectal cancer patients administered TIVA and IA in Asia (HR, 0.77; 95% CI, 0.57-1.05), and not in Europe (HR, 0.99; 95% CI, 0.93-1.06).Regarding tumour location, no significant association was found between TIVA and IA in the colon, rectum and colorectum ((HR, 0.70; 95% CI, 0.38-1.28), (HR, 0.95; 95% CI, 0.83-1.08) and (HR, 0.99; 95% CI, 0.93-1.06), respectively).Conclusion: OS differed significantly between patients administered TIVA and IA when undergoing colorectal cancer resection, but no difference was observed in RFS. The prognostic effects of TIVA and IA differed.